Considerations on the distribution and administration of the new COVID-19 vaccines. (2nd January 2021) - Kimble, Craig; Coustasse, Alberto; Maxik, Kenneth
ABSTRACT: The current system for approval of vaccines has been accomplished through multiple agencies worldwide. The World Health Organization (WHO) listed 40 candidate vaccines in clinical evaluation from different countries, including the United States, Russia, China, and the United Kingdom. These vaccines currently use at least seven different scientific approaches and involving technology using mRNA and DNA. Others include replication-defective viral-vectors, replicating viral-vectors, whole-killed virus, live-attenuated virus, and purified viral protein. The National Academies of Sciences, Engineering, and Mathematics created a framework for the equitable allocation of COVID-19 vaccines. Using this framework as a basis combined with work done at Johns Hopkins, the Centers for Disease Control and Prevention and WHO have reviewed public comments to the framework along with expert recommendations and have defined a "prioritization matrix" to ensure the safety and effectiveness of COVID-19 vaccines. This matrix is critical for planning the initial and ongoing distribution of vaccine doses. Initial indications are facilities would pay from US 4.00 up to US 145 per administration, even if the patient does not pay a fee. The international community's final prioritization matrix should communicate the efficient distribution protecting the essential workers and groups at high-risk COVID-19 to ensure high safety and efficacy.